-2x+3=19+6x

Simple and best practice solution for -2x+3=19+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+3=19+6x equation:


Simplifying
-2x + 3 = 19 + 6x

Reorder the terms:
3 + -2x = 19 + 6x

Solving
3 + -2x = 19 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
3 + -2x + -6x = 19 + 6x + -6x

Combine like terms: -2x + -6x = -8x
3 + -8x = 19 + 6x + -6x

Combine like terms: 6x + -6x = 0
3 + -8x = 19 + 0
3 + -8x = 19

Add '-3' to each side of the equation.
3 + -3 + -8x = 19 + -3

Combine like terms: 3 + -3 = 0
0 + -8x = 19 + -3
-8x = 19 + -3

Combine like terms: 19 + -3 = 16
-8x = 16

Divide each side by '-8'.
x = -2

Simplifying
x = -2

See similar equations:

| 5m=0.95 | | u^5-13u^2+36=0 | | 8(8)-11= | | 4-x+7+5x= | | -2x-5-2(x-3)=9x-(7x-8)-8x+5 | | -6(10+8)+9(5r+8)= | | -39-35= | | 5.5t=22 | | 4x+9=47 | | 3y-4/5y=22 | | -8-5f=12-9f | | 65+(4x-1)=180 | | 19-2n=-9 | | 2(x-10)+4x=-6x+2 | | n/8=28/32 | | 3y-4y=22 | | 8f=36 | | -18w-3+3w-12= | | -2x-5-2(x-3)=2x-(7x-8)-8x+5 | | -3(-3)+4(-4)= | | -3(-7)+4(-7)= | | 6*6n=96 | | y=4sin(x+pi) | | 46774x-86=64774+67x | | 748=x*880 | | 2x+14+x+20=180 | | -3(-9)+4(2)= | | f-4=9 | | -3(-9)+4(2)y= | | x+y=77 | | 15x+20(((3x+1)3)-5)=875 | | 5w-8m=z-4 |

Equations solver categories